2015
DOI: 10.1038/srep14145
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequencing demonstrates that Geographic Variation of Escherichia coli O157 Genotypes Dominates Host Association

Abstract: Genetic variation in an infectious disease pathogen can be driven by ecological niche dissimilarities arising from different host species and different geographical locations. Whole genome sequencing was used to compare E. coli O157 isolates from host reservoirs (cattle and sheep) from Scotland and to compare genetic variation of isolates (human, animal, environmental/food) obtained from Scotland, New Zealand, Netherlands, Canada and the USA. Nei’s genetic distance calculated from core genome single nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 45 publications
(58 reference statements)
1
50
0
Order By: Relevance
“…Similarly, a large-scale WGS study of Salmonella Typhi isolates from across the world identified a specific MDR clone that emerged in Asia and Africa with subsequent inter-and intracontinental transmission events (41). Importantly, our findings are also consistent with a WGS-based study (42) of Escherichia coli O157 isolates from different sources (e.g., animals, humans, and the environment/food) and different countries and continents. This study reported significant genetic differences among isolates from different geographical regions and hypothesized that a combination of local emergence events and international transmission leads to a "patchwork" of geographically confined and widely distributed clades.…”
Section: Discussionsupporting
confidence: 78%
“…Similarly, a large-scale WGS study of Salmonella Typhi isolates from across the world identified a specific MDR clone that emerged in Asia and Africa with subsequent inter-and intracontinental transmission events (41). Importantly, our findings are also consistent with a WGS-based study (42) of Escherichia coli O157 isolates from different sources (e.g., animals, humans, and the environment/food) and different countries and continents. This study reported significant genetic differences among isolates from different geographical regions and hypothesized that a combination of local emergence events and international transmission leads to a "patchwork" of geographically confined and widely distributed clades.…”
Section: Discussionsupporting
confidence: 78%
“…), and 7·7% in Scotland (Strachan et al . ). In another study performed in Argentina on retail meat, and butcher shop environmental samples, Galli et al .…”
Section: Resultsmentioning
confidence: 97%
“…In principle, this should enable discovery of large numbers of markers (e.g. SNPs) which have the potential to achieve unprecedented source attribution accuracy [31][32][33][34][35][36] . The challenge lies in efficiently mining large data sets for source attribution.…”
Section: Introductionmentioning
confidence: 99%